Interactive applications using Matplotlib : don't just see your data, experience it! - Root, Benjamin V. (Community experience distilled., 2015)
This book is intended for Python programmers who want to do more than just see their data. Experience with GUI toolkits is not required, so this book can be an excellent complement to other GUI programming resources.